Associations among diffusion tensor imaging and neurocognitive function in survivors of pediatric brain tumor: A pilot study. Issue 2 (3rd April 2021) - Aleksonis, Holly A.; Wier, Ryan; Pearson, Matthew M.; Cannistraci, Christopher J.; Anderson, Adam W.; Kuttesch, John F.; Compas, Bruce E.; Hoskinson, Kristen R.
Abstract: The purpose of this study was to determine associations among neurocognitive outcomes and white matter integrity in the inferior fronto-occipital fasciculus (IFOF), uncinate fasciculus (UF), and genu of the corpus callosum (gCC) in survivors of pediatric brain tumor and healthy controls (HCs). Eleven survivors (ages 8–16; >2 years post-treatment) and 14 HCs underwent MRI; diffusion tensor imaging tractography (DSI Studio) was used to assess white matter integrity. Participants completed neuropsychological assessment of overall cognitive ability, executive function, processing speed, divided attention, and memory. As previously reported, survivors performed significantly worse than HCs on measures of overall IQ, working memory, processing speed, and executive function ( p s < .01), but not on measures of long-delay memory. Mean fractional anisotropy was significantly lower in survivors than HC in the right IFOF, left UF, and gCC ( p s < .05). Correlations with the total sample revealed a number of significant positive associations among white matter tracts and scores on neurocognitive measures. Survivors show deficits on measures of cognitive function and decreased white matter integrity compared to HCs. Results revealed a more general pattern of associations among white matter pathways and neurocognitive outcomes than initially hypothesized. It is possible that survivors with diffuse pathology from treatment effects (i.e., hydrocephalus or posterior fossa syndrome) show more general decreases in cognitive functioning and white matter integrity. Additional research with a larger and more diverse group of survivors is needed to better understand white matter integrity and neurocognitive outcome associations in this population.